Water Infrastructure Impacts of Agricultural Industry in China Under Extreme Weather: A System Dynamics Model of a Multi-Level, Climate Resilience Perspective - Jiawen Li; Changzheng Zhang; Qiaozhi Huang; Mengyao Ding; Yuxin He; Mulan Liu; Chuchu Yang (Systems)
China is the world’s largest agricultural country and is also deeply affected by extreme weather. Water infrastructure is a crucial solution to improve the climate adaptability of the agricultural industry. This study aimed to explore the above adaptive processes of the agricultural industry from a resilience perspective. This study builds a multi-level system dynamics (SD) model to assess the development of the agricultural industry and water infrastructure, predict the future resilience development trend, identify the key influencing factors, and simulate the effectiveness of different water infrastructure measures. The results show that (1) water infrastructure involving various climate adaptation measures significantly promotes the development of the agricultural industry. (2) Agricultural output, water infrastructure investment, and other fixed asset investments strongly improve the resilience, and the impact of the crop planting area is limited. (3) The resilience level is higher under the eco-friendly water conservation scenario than in the water supply security scenario and flood disaster prevention scenario. Such information will promote the sustainable development of the agricultural industry and future climate adaptation policy-making.